MECHANICAL AND MICROSTRUCTURE PROPERTIES EVALUATION OF SIMILAR THIN AA7075-T6 WELDS BY REFILL FRICTION STIR SPOT WELDING - YAMIN, MOHD FADILLAH (2021)
Helmholtz-Zentrum Geesthacht GmbH, Germany has invented a new welding technique called refill Friction Stir Spot Welding to cater demands from aviation industry in producing lightweight aircraft.